The depiction of Norse gods archetypes in Neil Gaiman’s Norse Mythology - Gabriel Erlangga; Ni Made Widisanti Swetasurya; Jordy Satria Widodo (Universitas Pakuan, 2025)
This research examines the depiction of key archetypal figures from Norse mythology in Neil Gaiman’s Norse Mythology, utilizing Carl Gustav Jung’s analytical psychology as the theoretical framework. The analysis focuses on three central characters: Odin, Thor, and Loki, interpreted as representations of the archetypes: The Wise Old Man, The Hero, and The Trickster. The study employs a qualitative descriptive method and interpretative content analysis. The findings indicate that the novel reconfigures their symbolic meanings within a narrative structure that reflects the psychological dynamics of contemporary individuals. Odin is presented as a contemplative spiritual leader, Thor as a hero who transforms failure through introspection, and Loki as the embodiment of creative chaos. Through this archetypal lens, the novel effectively conveys the structure of the human unconscious collective. This research concludes that Norse mythology serves as a bridge, linking the symbolic legacy of the past with modern narratives and contemporary existential exploration.